Kewenangan Otoritas Jasa Keuangan (OJK) Melakukan Penyidikan: Analisis Pasal 9 Huruf C Undang-Undang Nomor 21 Tahun 2011 Tentang Otoritas Jasa Keuangan - Serlika Aprita (Jurnal Ilmiah Universitas Batanghari Jambi, 2021)
In Law No. 21 of 2011 concerning the Financial Services Authority authorizes the OJK to carry out investigations. Investigation is one of OJK's supervisory duties as referred to in Article 9 letter c of the OJK Law which reads: "To carry out the supervisory duties as referred to in Article 6, OJK has the authority to carry out supervision, examination, investigation, consumer protection, and other actions against Service Institutions. Finance, actors and / or supporting financial services activities as referred to in the laws and regulations in the financial services sector. " According to Article 49 paragraph (1) of Law No. 21 of 2011 concerning Financial Services Authority (OJK), OJK Investigators are: 1. Apart from Investigating Officers of the State Police of the Republic of Indonesia, certain Civil Servants whose scope of duties and responsibilities includes supervision financial services sector within the OJK, given special authority as investigators as referred to in the Criminal Procedure Code. The research method in this paper is to use normative legal research. The regulation regarding the role of the OJK as an investigator is regulated in article 9 letter (c) of Law No. 20 of 2011 concerning the Financial Services Authority which becomes the basis for OJK in conducting investigations of banking crimes, so that the OJK carries out the function of implementing an integrated regulatory and supervisory system of all activities in the financial services sector.